"I was giving someone who didn't have a voice a voice": exploring qualitative mini-research projects as a tool to teach students about aging. Issue 6 (2nd June 2020) - Neiterman, Elena; Sheppard, Christine; Kassam, Souraiya; Bach, Vanessa; Husain, Saman
ABSTRACT: In the study of gerontology, fieldwork with older adults is often used to enhance students' understanding of the aging process. While assignments based on interactions with older adults are a common practice in teaching students enrolled in gerontology studies, we know less about the impact of such activities on students from other disciplines. This paper summarizes students' experiences with an assignment offered to a diverse cohort of undergraduate students who took a course in social gerontology. To complete this assignment, students had to interview an older adult, summarize the life story of the participant, apply a theoretical perspective to the older adult's life story, and reflect on the process. Analyzing data derived from 72 assignments and 10 semi-structured interviews with students who were enrolled in the course, this paper examines students' experiences with this assignment. Specifically, we identify what aspects of the assignment students found beneficial, what aspects they found challenging, and in what ways this assignment helped students to enhance their understanding of aging. Our findings suggest that students found it challenging to recruit an older adult for an interview and struggled with the semi-structured nature of the interview process. All students found the actual interview process to be extremely rewarding and beneficial for their learning. In discussion, we provide some recommendations on how to offer this type of assignment to a diverse group of students enrolling in the courses on social gerontology.